Месть Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 1995)
Экземпляры: аб. ЦБ (20191202) / Инвентарный номер: 8248 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 71 / ББК: 84(2Рос=Рус)6